Simulator training in focus assessed transthoracic echocardiography (FATE) for undergraduate medical students: results from the FateSim randomized controlled trial - Weimer, Johannes Matthias; Sprengart, Franziska Marietta; Vieth, Thomas L.; Göbel, Sebastian; Dionysopoulou, Anna; Krüger, Rebecca; Beer, Jan; Weimer, Andreas; Buggenhagen, Holger; Klöckner, Roman; Pillong, Lukas; Helfrich, Johanna; et al. (BMC medical education, 2025)
Ultrasound is important in heart diagnostics, yet implementing effective cardiac ultrasound requires training. While current strategies incorporate digital learning and ultrasound simulators, the effectiveness of these simulators for learning remains uncertain. This study evaluates the effectiveness of simulator-based versus human-based training in Focused Assessed with Transthoracic Echocardiography (FATE).
Gesehen am 13.11.2025